2016
DOI: 10.1016/s2352-3018(16)00046-1
|View full text |Cite
|
Sign up to set email alerts
|

Near real-time monitoring of HIV transmission hotspots from routine HIV genotyping: an implementation case study

Abstract: BackgroundDue to the rapid evolution of HIV, infections with similar genetic sequences are likely to be related by recent transmission events. Clusters of related infections can represent subpopulations with high rates of HIV transmission. Here we describe the implementation of an automated “near real-time” system using clustering analysis of routinely collected HIV resistance genotypes to monitor and characterize HIV transmission hotspots in British Columbia (BC).MethodsA monitoring system was implemented on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
163
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(167 citation statements)
references
References 30 publications
2
163
0
Order By: Relevance
“…Unfortunately, the time delay between HIV diagnosis/interview and genotype acquisition by the DOHMH (i.e., 6 months in our study, though this delay has shrunk since 2012) represents an impediment to prompt network-based intervention. Point-of-diagnosis-genotyping coupled with real-time genetic network analysis to identify potential transmission partners could help interdict ongoing transmission and target prevention, linkage to care, and treatment more effectively (as recent suggested in [18]).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the time delay between HIV diagnosis/interview and genotype acquisition by the DOHMH (i.e., 6 months in our study, though this delay has shrunk since 2012) represents an impediment to prompt network-based intervention. Point-of-diagnosis-genotyping coupled with real-time genetic network analysis to identify potential transmission partners could help interdict ongoing transmission and target prevention, linkage to care, and treatment more effectively (as recent suggested in [18]).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all uses of genetic clustering to infectious diseases have occurred in the context of retrospective studies, in which clusters are identified at a fixed point in time and seldom revisited in subsequent studies. In settings where there is widespread access to routine HIV genotyping, however, it is possible to prospectively track the appearance of new infections in clusters in real time (Little et al 2014; Poon et al 2016). Regardless of the inherent biases of genetic clustering methods, observing a rapid succession of new infections in a predefined cluster may represent an important source of evidence of a localized outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…A sequence was classified as clustered if its shortest patristic distance to another sequence was below the cutoff in 80% or more of the bootstrap trees. This is the same clustering method being used for near real-time monitoring of HIV hotspots in British Columbia, Canada (Poon et al 2016). …”
Section: Evaluation Of Clustering Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic methods can be used to study HIV transmission networks and hotspots within communities and populations 810 and to assess the genetic linkage of specific transmission events. 4,11 In this study, we used phylogenetic and statistical methods to identify genetically-linked partner infections in the HPTN 052 trial, which were the basis of the primary endpoint analysis for this landmark study.…”
Section: Discussionmentioning
confidence: 99%